Predictors of Long-Term Disease Control and Survival for HER2-Positive Advanced Breast Cancer Patients Treated With Pertuzumab, Trastuzumab, and Docetaxel - Hopkins, Ashley M.; Rowland, Andrew; McKinnon, Ross A.; Sorich, Michael J. (Frontiers in Oncology, 2019)
Background HER2-positive advanced breast cancer (ABC) is associated with significant heterogeneity in long-term disease control and survival. Prognostic models for HER2-positive ABC patients considering first-line pertuzumab, trastuzumab and docetaxel have not been evaluated. Methods A pre-treatment prognostic model for progression-free survival (PFS) and overall survival (OS) was developed for HER2-positive ABC patients initiating first-line pertuzumab, trastuzumab and docetaxel using clinicopathological data from the randomised clinical trial CLEOPATRA (n=408). Cox proportional hazard analysis with a backwards deletion process was used. Results Metastatic sites count (< 3 versus ≥ 3) and lactate dehydrogenase (LDH) (≤ ULN versus > ULN) were identified as common pre-treatment risk predictors for PFS and OS (P < 0.05). Based on these two factors, patients can be characterised as one of three prognostic groups (good = 0 factors; intermediate = 1 factor; poor = 2 factors). The prognostic groups were associated with significantly different PFS (P < 0.001), with 3-year PFS probabilities of 44% (36-55), 28% (22-36) and 17% (11-29) for the good, intermediate and poor prognostic groups, respectively. Similarly, there was significant differences in OS (P < 0.001), with 4-year OS probabilities of 75% (95%CI: 67-84), 60% (53-68) and 31% (21-45) for the good, intermediate and poor prognostic groups, respectively. Conclusions Pre-treatment prognostic groups identified for HER2-positive ABC patients initiating first-line pertuzumab, trastuzumab and docetaxel had significantly different long-term disease control and survival outcomes.